2021
DOI: 10.1002/nop2.1013
|View full text |Cite
|
Sign up to set email alerts
|

Frontline nurses' experiences of working in a COVID‐19 ward–A qualitative study

Abstract: Aim To explore how nurses experienced working in a newly organized COVID‐19 ward with high‐risk patients during a new and unknown pandemic. Design A qualitative explorative study using a phenomenological‐hermeneutic approach. Methods Semi‐structured individual telephone interviews were conducted in June–July 2020 with 23 nurses working in COVID‐19 wards from three regional hospitals in Denmark. The nurses had been transferred from other depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…In particular, frontline nurses who were caring for COVID-19 patients reported that they experienced significant anxiety, which was related to their stress from work, whereas their rights were relatively ignored in the crisis (7,8). Similarly, research on psychiatric problems of healthcare workers treating other infectious diseases showed that they were vulnerable to severe emotional distress, depression, anxiety, and even posttraumatic stress disorder (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, frontline nurses who were caring for COVID-19 patients reported that they experienced significant anxiety, which was related to their stress from work, whereas their rights were relatively ignored in the crisis (7,8). Similarly, research on psychiatric problems of healthcare workers treating other infectious diseases showed that they were vulnerable to severe emotional distress, depression, anxiety, and even posttraumatic stress disorder (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al, (2020) argue that the superhero metaphor presupposes a transcendent being not requiring of decent wages, dedicated to high calibre care at personal cost. However, as identified in the current research, altruism also fostered resilience in some participants; a point noted in some studies (Specht et al, 2021;Wang et al, 2020). By 12 June 2020, 96 healthcare and support workers had acquired COVID-19 in their workplace; 6.4% of total infections (Ministry of Health, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Given that in light of the coronavirus pandemic such situations were a daily occurrence, nursing professionals' strong (empathybased) responses to these situations were a daily occurrence, too. It is true that nursing practitioners have unique experiences of working in a COVID-19 ward and have to overcome extreme, totally new and unpredictable situations which they experience as challenging and uncertain [44]. These experiences make it more likely nursing practitioners will suffer posttraumatic stress symptoms and have profound negative impact on their psychological health [45].…”
Section: Discussionmentioning
confidence: 99%